2021
DOI: 10.1200/jco.2021.39.15_suppl.e17022
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and comorbidities of veterans treated with enzalutamide or abiraterone.

Abstract: e17022 Background: Prostate cancer (PCa) is the most common male malignancy and is the fourth leading cause of cancer-related death in males worldwide. Enzalutamide (ENZ) and Abiraterone (AA) are used in the treatment of castrate resistant PCa after androgen deprivation therapy (ADT), however these agents have not been directly compared. These drugs have various adverse effects with different mechanisms of action and may be selected based on comorbid conditions. In this study, we aim to identify patient chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Large retrospective studies of the Veterans Health Administration show that veterans prescribed enzalutamide tend to be older (74.2 versus 73.7 years, p = 0.032), have higher Elixhauser comorbidity scores (7.1 versus 6.7, p = 0.002), and remain on treatment longer (10.5 months versus 9.0 months, p < 0.001) than those who were prescribed abiraterone. 70 A more focused assessment of veterans with chemotherapy naïve mCRPC found that even with adjusting for baseline comorbidity, enzalutamide-treated patients had a 16% reduced risk of death (HR: 0.84; 95% CI: 0.76–0.94; p = 0.0012) compared to those treated with abiraterone. These differences could be due to the well-established cardiovascular toxicities of abiraterone.…”
Section: Geriatric Assessment and Arpismentioning
confidence: 99%
“…Large retrospective studies of the Veterans Health Administration show that veterans prescribed enzalutamide tend to be older (74.2 versus 73.7 years, p = 0.032), have higher Elixhauser comorbidity scores (7.1 versus 6.7, p = 0.002), and remain on treatment longer (10.5 months versus 9.0 months, p < 0.001) than those who were prescribed abiraterone. 70 A more focused assessment of veterans with chemotherapy naïve mCRPC found that even with adjusting for baseline comorbidity, enzalutamide-treated patients had a 16% reduced risk of death (HR: 0.84; 95% CI: 0.76–0.94; p = 0.0012) compared to those treated with abiraterone. These differences could be due to the well-established cardiovascular toxicities of abiraterone.…”
Section: Geriatric Assessment and Arpismentioning
confidence: 99%